Mathematics beliefs questionnaire: psychometric properties - Rincón-Álvarez, Gerson Adriano; Hernández-Suárez, Cesar Augusto; Prada Núñez, Raúl; Solano-Pinto, Natalia; Fernández-Cézar, Raquel (Instituto para la Investigación Educativa y el Desarrollo Pedagógico, IDEP, 2022)
This article describes the confidence analysis of the contextualization of the “Affective Mastery in Solving Mathematical Problems”, in what corresponds to the beliefs about mathematics to obtain a contextualized and reliable instrument with which the beliefs of Colombian students of basic and secondary education about mathematics can be identified and characterized, differentiating whether or not they belong to contexts of social vulnerability. A probabilistic test was carried out using the multilevel conglomerate method, leaving the sample made up of 1039 students from Cúcuta and Villa del Rosario, with a mean age of 13.76 years and a standard deviation of 2.34 years. The reliability of the contextualization of the instrument gave a Cronbach's alpha coefficient of 0.940 for both the total instrument and values ​​from acceptable to high for each of the dimensions. The Spearman-Brown coefficient for equal length gives a correlation value of 0.920, as well as the Guttman half-dose coefficient gave 0.918, as well as acceptable values ​​from low to high for each of the dimensions that make up the instrument. Confirmatory factor analysis (CFA) ratifies the four dimensions or factors theoretically, It is concluded that the contextualization of the instrument to evaluate the beliefs about the mathematics carried out presents a high statistical internal consistency and a high degree of reliability. This conclusion makes it an adequate instrument for the study of beliefs in students in the Colombian context.